Dawn of the dialogue: AI's leap from lab to living room - Procko, Tyler Thomas; Elvira, Timothy; Ochoa, Omar (Frontiers in Artificial Intelligence, 2024)
Prior to the advent of mainstream Large Language Models, e.g., ChatGPT, there were two contexts of AI use: theoretical and technical. The former involves the mathematics behind AI constructs, as well as new AI research; the latter encompasses the substance of AI use, i.e., programming, training, execution, etc. With the recent proliferation of Large Language Models for content generation, such as texts, images, and videos, there arises a new context of AI use: practical. This aspect of AI use is unique, in that practical users do not need theoretical or technical AI knowledge to prosper: they need only know how to prompt. In effect, the practical context of AI use is a black-box approach. These three contexts of AI converge in a unique intersection of AI knowledge. This emerging AI perspective is important to consider, as most AI users, now and in the future, will possess no deep knowledge of AI.